Girls in love - Wilson, Jacqueline (London : Corgi, 2007)
Ellie, a normal, ordinary girl, starts ninth grade with high hopes of keeping her best friends, staying on a diet, becoming more glamorous, and getting a boyfriend.
"First published in Great Britain by Doubleday ... 1997"--T.p. verso.
7.8
5-8
Keywords: Man-woman relationships -- Fiction; Schools -- Fiction; Teenage girls -- Fiction; Girls -- Fiction; Man-woman relationship -- Fiction; School stories; Teenagers -- Fiction